Restricted mobility of specific functional groups reduces anti-cancer drug activity in healthy cells - Martins, Murillo L. [UNESP]; Ignazzi, Rosanna; Eckert, Juergen; Watts, Benjamin; Kaneno, Ramon [UNESP]; Zambuzzi, Willian F. [UNESP]; Daemen, Luke; Saeki, Margarida J. [UNESP]; Bordallo, Heloisa N. (Nature Publishing Group, 2016)
The most common cancer treatments currently available are radio- and chemo-therapy. These therapies have, however, drawbacks, such as, the reduction in quality of life and the low efficiency of radiotherapy in cases of multiple metastases. To lessen these effects, we have encapsulated an anti-cancer drug into a biocompatible matrix. In-vitro assays indicate that this bio-nanocomposite is able to interact and cause morphological changes in cancer cells. Meanwhile, no alterations were observed in monocytes and fibroblasts, indicating that this system might carry the drug in living organisms with reduced clearance rate and toxicity. X-rays and neutrons were used to investigate the carrier structure, as well as to assess the drug mobility within the bio-nanocomposite. From these unique data we show that partial mobility restriction of active groups of the drug molecule suggests why this carrier design is potentially safer to healthy cells.